PERALIHAN WALI NASAB KEPADA WALI HAKIM DALAM PERNIKAHAN PERSPEKTIF HUKUM ISLAM (Studi di Kantor Urusan Agama Kecamatan Pare Kabupaten Kediri) - Nurjani Mutiara Pattiasina; Arianto (Institut Agama Islam Hasanuddin Pare, 2024)
Article 19 of the Compilation of Islamic Law (KHI) indeed emphasizes that a marriage guardian is one of the pillars in the implementation of a marriage contract. In marriage, the existence of a guardian is a requirement that must be met so that the marriage is considered valid according to Islamic law and also the positive law in force in Indonesia. In Islamic law, a woman is not allowed to marry herself, so the existence of a guardian is one of the pillars of marriage that must be met so that the marriage is valid. The guardian has an important role in marrying the bride, representing the family, and ensuring that the marriage is in accordance with sharia. Marriage guardians are divided into two types, namely lineage guardians and judge guardians. This study uses a field research method by collecting data through observation and interviews at the KUA, Pare District. The approach used is normative juridical, which refers to applicable legal norms, with qualitative analysis using the inductive method to draw conclusions from the data collected. The results of this study conclude that the transfer of lineage guardians to judge guardians in marriages at the Pare KUA in 2020-2024 was caused by several main factors, namely guardians of different religions (the parents of the prospective bride are not Muslim), mafqud guardians (whereabouts unknown), running out of lineage guardians, and adhal guardians (guardians who refuse or are rebellious). From an Islamic law perspective, the implementation of marriages with judge guardians at the Pare KUA during this period was declared valid, because it was in accordance with the principles of Islamic law and complied with the Regulation of the Minister of Religion Number 20 of 2019 Article 13, which stipulates that in the absence of lineage guardians, the marriage contract can be carried out with a judge guardian.